2022
DOI: 10.3390/vetsci9100531
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanism of siRNAs Targeting IL-1β/TNF-α Combined with BMSCs Transplantation in Ameliorating Rheumatoid Arthritis in Rats

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune disease. Bone marrow mesenchymal stem cells (BMSCs) have multilineage differentiation and anti-inflammatory potential, and small interfering RNAs (siRNAs) can inhibit the target gene expression, which make them suitable for ameliorating RA. The current study was aimed to explore the effect and potential mechanisms of siRNAs targeting IL-1β/TNF-α combined with BMSCs transplantation in ameliorating RA in rats. Methods: Collagen-induced arthritis (CIA) model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…BMSCs were isolated from ten four-week-old female Wistar rats as previously described, respectively. 10 The BMSCs were cultured with α-MEM containing 10% fetal bovine serum and 1% cyanstreptomycin in a humidified incubator at 37 °C and 5% CO 2 . In vitro differentiation assays were conducted on BMSCs that had undergone two passages of cultured expansion.…”
Section: Culture and Characterization Of Bmscsmentioning
confidence: 99%
See 2 more Smart Citations
“…BMSCs were isolated from ten four-week-old female Wistar rats as previously described, respectively. 10 The BMSCs were cultured with α-MEM containing 10% fetal bovine serum and 1% cyanstreptomycin in a humidified incubator at 37 °C and 5% CO 2 . In vitro differentiation assays were conducted on BMSCs that had undergone two passages of cultured expansion.…”
Section: Culture and Characterization Of Bmscsmentioning
confidence: 99%
“…Numerous evidence demonstrated that BMSCs are the hotspots of cellular therapy and tissue repair due to their low immunogenicity, potent immunoregulation, and homing ability, which enables them to move from niche to peripheral circulation and pass through the vascular wall to reach the target tissue . Then, BMSCs play an important role in treating diseases such as arthritis, cardiac fibrosis, and spinal cord injury, , mainly by differentiating into local components of injured area and secreting chemokines, cytokines, and growth factors . Although much evidence proved the superior efficacy of BMSCs in various disease models, BMSCs may cause immune rejection, teratoma formation, and cell nondifferentiation after implantation. , To avoid this possible safety issue, greater attention has focused on developing cell-free therapeutics in stem cell therapy. , Therefore, the replacement of stem cells with stem cell-derived exosomes (Exos) has become a viable alternative and has received increasing attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panet et al examined the effects of simultaneous therapy with both BM‐MSC and siRNAs targeting IL‐1β/TNF‐α in CIA model rats. They concluded the therapy with siRNA and BM‐MSC showed synergism effects on alleviating the inflammation and cartilage repair of RA rats 77 …”
Section: Msct In Ramentioning
confidence: 99%